2011
DOI: 10.1080/07481187.2011.553316
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Living and Their Moderating Effects on Korean Adolescents' Suicidal Ideation

Abstract: The present study validated the use of the Korean version of the Reasons for Living Inventory for Adolescents (KRFL-A) in a group of 406 South Korean high school students. Confirmatory factor analysis confirmed the original 5-factor and other psychometric properties demonstrated the usefulness of the KRFL-A as a measure of cognitive protective factors. Hierarchical regression analyses revealed that the KRFL-A total significantly moderated the impact of depressive symptoms on suicidal ideation. More specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 21 publications
6
34
0
Order By: Relevance
“…We also found the association between entrapment and suicidal ideation was moderated by reason for living. This result supports previous research suggesting that reason for living may weaken the association between suicidal risk factors and suicidal ideation, acting as a buffer (e.g., Bakhiyi et al, 2016;Britton et al, 2008;Johnson et al, 2011;Lee, 2011;Salami et al, 2015). According to the buffering hypothesis proposed by Johnson et al (2011), only factors that appear to have a moderating impact upon risk and suicidality can be viewed as a resilience or buffer variable for suicidality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also found the association between entrapment and suicidal ideation was moderated by reason for living. This result supports previous research suggesting that reason for living may weaken the association between suicidal risk factors and suicidal ideation, acting as a buffer (e.g., Bakhiyi et al, 2016;Britton et al, 2008;Johnson et al, 2011;Lee, 2011;Salami et al, 2015). According to the buffering hypothesis proposed by Johnson et al (2011), only factors that appear to have a moderating impact upon risk and suicidality can be viewed as a resilience or buffer variable for suicidality.…”
Section: Discussionsupporting
confidence: 89%
“…Second, reason for living was linked to lower levels of risk factors for suicidal ideation, such as depression (e.g., Bagge, Lamis, Nadorff, & Osman, 2014), hopelessness (e.g., Bagge et al, 2014) and impulsivity (Salami et al, 2015). Third, reason for living has also been found to weaken the associations between suicidal risk factors (e.g., depression, hopelessness, and impulsivity; Britton et al, 2008;Lee, 2011;Salami et al, 2015) and suicidal ideation. Taken together, these results consistently suggested that high levels of reason for living may protect against the development of suicidal ideation.…”
Section: The Protective Role Of Reason For Living In Suicidal Ideatiomentioning
confidence: 99%
“…A sense of unhappiness may play a role in the higher incidence of suicidal ideation in Korea. The present findings demonstrate the importance of considering risk factors and protective factors in assessing suicidal ideation among Korean adolescents (Lee, 2009). Indeed, eliminating risk factors is not always possible when intervening with suicidal individuals.…”
Section: Discussionmentioning
confidence: 69%
“…In previous studies, the factors that affect the adolescent suicidal ideation rate were condensed into depression, stress [4,[9][10][11][12], hopelessness [2,3,14], low self-esteem [15,16], absence of social support [2,3,5,11,15], bullying [4,18], conflict with one's parents [4,12,16,17], and poor peer relationships [4,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%